The emergence of Smartphones: An exploratory study of consumer attitude and intention to redeem mobile coupons - Lao, Ka Man (2012)
Purpose - The prevalence of mobile phones, especially the development of smartphones, has attracted numerous companies to exploit the potential in mobile marketing. One notable mobile marketing tool that is progressively gaining interest is the mobile coupon. The aim of this study is to build a conceptual model to explain consumers’ attitude and intention to redeem mobile coupon in the emergence of smartphones. Design/methodology/approach – This study is based on an online survey questionnaire of 166 respondents. The collected data is mainly analysed through exploratory factor analysis and linear regression analysis. Findings – The results indicate that attitude towards mobile coupons is positively affected by economic benefits, location-based service and entertainment, while the redemption effort exhibits a direct negative effect on attitude. In regard to the intention to redeem mobile coupons, results show attitude and past behaviour have a significant direct influence on intention, while the perceived control and subjective norm are not evident. Research implications/limitations – This study validates the applicability of the adoption models in explaining consumers’ acceptance in mobile marketing, in particular a more profound understanding is provided in the mobile coupon context. Practical implications - The results of this study provides noteworthy insights for marketers and advertisers in planning their mobile coupons promotions in an effective way. It is suggested marketers should not only consider the monetary motive, but also the hedonistic and non-utilitarian motives. Originality/Value – The topic of mobile marketing is in its early stages and limited studies have particularly explored the phenomenon of mobile coupons in the era of smartphones. This study makes an effort in fulfilling the need for research evidence and contributes to the contemporary mobile marketing research.